Biostratigraphy, taxonomy and paleobiogeography of the upper Cisuralian (upper Yakhtashian–Bolorian) foraminifers from east-central Iran, with clarification of the taxonomy of the fusulinid genera Cuniculinella and Cuniculina pre-occupied. (February 2021) - Sharahi, Safoora Yasbolaghi; Yeganeh, Bizhan Yousefi; Arefifard, Sakineh; Vachard, Daniel; Farahpour, Mohammad Mehdi
Abstract: Detailed studies of upper Cisuralian (i.e., upper lower Permian) fusulinids make it possible to decipher the paleobiogeographic relations of central Iran, as part of the Cimmerian terranes, with other Paleotethyan regions. Two sections, Bagh-e Vang and Shesh Angosht, located in east-central Iran, are revised. Four local fusulinid biozones are distinguished: upper Yakhtashian Pamirina darvasica and Sakmarella spp. Zone, lower Bolorian Misellina ( Brevaxina ) dyrhenfurthi Zone, mid-Bolorian Cuniculinella Zone, and upper Bolorian Misellina ( Misellina ) cf. M . ( M .) termieri Zone (probably equivalent to the traditional Misellina ( Brevaxina ) parvicostata Zone). Taxonomically, the main results are as follows: (1) a clarification is provided of the fusulinid genus or subgenus " Cuniculina, " the name of which is pre-occupied, and its synonymy with Cuniculinella ; and (2) a lectotype is designated for Darvasites ( Alpites ) sinensis (Chen, 1934 ). The mid-Bolorian Cuniculinella Zone is recognized for the first time in Iran. Among the Bolorian fusulinids, Cuniculinella is reported in SE Pamir, Karakoram, central Afghanistan, SW Japan, central Japan, and California, confirming the faunal affinity of the study area in east-central Iran with both Paleotethyan and Panthalassan bioprovinces. Such a distribution is considered to have resulted from combined effects of global warming during the upper Cisuralian, warm oceanic currents along the Paleotethys Ocean, and the northward drift of the Iran block toward lower paleolatitudes.